Communication Towers in the Business and City Aesthetic Aspects to Face the VUCA Challenges (Open Society Conference, 2023)
Communication towers are one of the important aspects that support business development in a city, while also considering aesthetic aspects. This research aims to see how the role of communication towers in facing VUCA challenges. Qualitative methods were used to collect various data developed in SWOT analysis. The results showed potential business aspects considered based on the strengths, weaknesses, opportunities, and threats of communication towers in addition to city aesthetics in facing VUCA challenges. The SWOT analysis of telecommunication towers and available land shows that the most successful strategies are the SO (Aggressive Supporting Strategy) and ST (Diversification Supporting Strategy) approaches. It is crucial to investigate accessible land and the contribution of the business to the community to determine the government's actual position. Four strategic options are generated from the SWOT approach presented in matrix form. The results of the SWOT analysis can be considered by stakeholders in utilizing the potential of this communication tower.